Neural correlates of egocentric and allocentric frames of reference combined with metric and non-metric spatial relations. (15th June 2019) - Ruotolo, F.; Ruggiero, G.; Raemaekers, M.; Iachini, T.; van der Ham, I.J.M.; Fracasso, A.; Postma, A.
Abstract: Spatial relations (SRs: coordinate/metric vs categorical/non metric) and frames of reference (FoRs: egocentric/body vs allocentric/external element) represent the building blocks underlying any spatial representation. In the present 7-T fMRI study we have identified for the first time the neural correlates of the spatial representations emerging from the combination of the two dimensions. The direct comparison between the different spatial representations revealed a bilateral fronto-parietal network, mainly right sided, that was more involved in the egocentric categorical representations. A right fronto-parietal circuitry was specialized for egocentric coordinate representations. A bilateral occipital network was more involved in the allocentric categorical representations. Finally, a smaller part of this bilateral network (i.e. Calcarine Sulcus and Lingual Gyrus), along with the right Supramarginal and Inferior Frontal gyri, supported the allocentric coordinate representations. The fact that some areas were more involved in a spatial representation than in others reveals how our brain builds adaptive spatial representations in order to effectively react to specific environmental needs and task demands. Highlights: Egocentric and Allocentric FORs have been combined with Categorical and Coordinate SRs. The neural correlates of the deriving combinations have been identified. Coordinate and Categorical Egocentric processing involved fronto-parietal areas. Coordinate and Categorical Allocentric processing involved occipital areas. Coordinate spatial relations were more supported by the right part of the brain.